Beyond the consensus criteria: multiple cognitive profiles in amyotrophic lateral sclerosis?. (August 2016) - Consonni, Monica; Catricalà, Eleonora; Dalla Bella, Eleonora; Gessa, Valentina C.; Lauria, Giuseppe; Cappa, Stefano F.
Abstract: The Strong consensus recommendations (2009) propose behavioural (ALSbi) and/or dysexecutive (ALSci) impairment as the two main clinical profiles of non-motor manifestations in non-demented amyotrophic lateral sclerosis (ALS) patients. We aimed at assessing whether clustering pattern of neuropsychological performance of ALS patients suggest the existence of additional clinical syndromes beyond the currently recognized phenotypes. We applied principal component analysis (PCA) to a comprehensive neuropsychological evaluation of 71 non-demented ALS patients in order to identify clusters of variables correlating highly with each other, with the aim of detecting distinct patterns of neuropsychological test performance. The outcome of PCA demonstrated the existence of three main test clusters. Two, accounting for 27% of the patients, were compatible with the recognised ALSbi and ALSci profiles. An additional third cluster loaded on social cognition, language and memory tests and accounted for 24% of the patients. Of these, 15% had defective performance on at least two tests belonging to the latter non-executive cluster, and were thus unclassifiable according to current criteria. Our data-driven approach indicated a third dimension of cognitive impairment, including language, social cognition and episodic memory, as a distinct pattern of non-motor manifestations in ALS patients, in addition to the recognized ALSci and ALSbi profiles.